The impact of the CEO’s green ecological experience on corporate green innovation—The moderating effect of corporate tax credit rating and tax burden - Wang, Lixia; Li, Yan; Lu, Sangying; Boasson, Vigdis (Frontiers in Environmental Science, 2023)
Using the data of listed companies in Chinese capital market from 2014 to 2020, this paper studies the impact of CEO’s green ecological experience on corporate green innovation, and further analyzes the moderating effect of tax credit rating and tax burden. The results show that: (1) CEO’s green ecological experience can enhance corporate green innovation; (2) China’s tax credit rating positively moderates the impact of CEO's green ecological experience on corporate green innovation; (3) Corporate tax burden will negatively moderate the impact of CEO's green ecological experience on corporate green innovation.